X‐band low‐phase noise oscillator employing substrate integrated waveguide dual‐mode filter. Issue 6 (1st March 2015) - Yang, Ziqiang; Luo, Bangyu; Dong, Jun; Yang, Tao
Abstract : A novel low‐phase noise oscillator employing a substrate integrated waveguide (SIW) dual‐mode bandpass filter as a frequency stabilisation element within its feedback loop is proposed. The SIW dual‐mode filter is implemented based on the use of the two degenerate modes (TE102 and TE201 ) and has a larger group delay peak than the conventional SIW cavity resonator. By taking advantage of the large group delay peak, the phase noise of the oscillator has significant improvement. An X‐band oscillator with a GaAs HEMT packaged transistor has been designed and measured. At an oscillation frequency of 9.04 GHz, the measured phase noise is −111.9 dBc/Hz at 100 kHz offset. The output power is 6.1 dBm and the figure of merit is −198 dBc/Hz.